Pre-service teachers as partners in climate change and health education - Ramadani, Lira; Rahimitabar, Parisa; Caka, Fjollë; Boeckmann, Melanie (Frontiers in Education, 2025)
University-based teacher preparation programs in Kosovo still lack climate and health education, leaving preservice teachers (PSTs) unprepared for addressing climate challenges. Considering that the climate crisis is one of the biggest global health challenges of the century, awareness among PSTs as future change agents regarding this issue is crucial. This study investigates how PSTs can be both learners and active contributors in the fields of climate change and health education as future change agents. A cross-sectional survey was conducted to assess the PSTs’ perceptions regarding climate change and health education, among a sample of 137 PSTs at the University of Prishtina - Kosovo. To gain deeper insights, 5 focus groups and 3 interviews with a total of 21 participants were conducted. Descriptive statistics were used for the surveys, and qualitative data from focus groups and interviews were analyzed through thematic analysis. There is a strong commitment among future educators to teach climate change and health topics, with most participants eager to include them in classrooms and willing to learn more. Focus groups emphasized the crucial role of teachers in shaping knowledge and behavior, highlighting preservice teachers’ motivation to integrate these vital topics into their future teaching. Gaps in teacher curricula highlighted the need for greater focus on these topics and more practical, experiential learning. The findings indicate a readiness and eagerness among future educators in Kosovo to learn and teach more about climate change and health, underscoring their potential role as partners in curriculum development. Through co-creation and student partnership initiatives, universities can harness the enthusiasm of future educators to integrate climate and health education into their teaching.